The effect of orthophosphoric acid on energy-intensive parameters of porous carbon electrode materials - Ivanichok, N.Ya.; Kolkovskyi, P.I.; Soltys, A.M.; Boychuk, V.M.; Mandzyuk, V.I.; Yablon, L.S.; Rachiy, B.I. (Physics and Chemistry of Solid State, 2023)
The effect of orthophosphoric acid concentration as an activating agent on the porous structure of carbon materials derived from apricot pits and energy-intensive parameters of electrochemical capacitors formed on their basis is studied. It is found that changing the ratio of the mass of the activating agent to the mass of the raw material in acid-activated porous carbon materials (PCMs), one can control the pore size distribution in the range of 0.5-20 nm and specific surface area in the range of 775-1830 m2/g. The use of cyclic voltammetry, impedance spectroscopy and chronopotentiometry made it possible to set the capacitive nature of charge accumulation processes in acid-activated PCMs, as well as to determine the contribution of a certain size of pores to the specific capacitance of PCM/electrolyte system.